American Indians in feature films: beyond the big Screen. Issue 4 (30th September 2014) - V. Domínguez, Daisy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine whether library collections accurately represent the breadth of portrayals of American Indians in feature film. It also provides collection development resources for developing and strengthening feature film collections by and about American Indians. Design/methodology/approach – This study compares WorldCat holdings of a sample of theatrically released films about American Indians with independent American Indian-made films. Findings – WorldCat holdings as a whole do not represent the breadth of portrayals of American Indians in feature film. Originality/value – There are no studies that examine library holdings of feature films by and about American Indians. This paper presents an opportunity to examine our collecting habits and recommends resources for building feature film collections that better represent the manifold Native American experience.